Ação cultural e biblioteca escolar: um estudo na rede pública estadual de ensino do município de Cacoal - RO - Passos, Naiara Raíssa da Silva (2023)
In this research, we consider that cultural action is configured as one of the possibilities for school libraries to act, taking into account the sociocultural context in which these institutions are inserted, as a space for teaching and learning, for reading words and the world, for socialization, democracy and cultural democratization. In this context, we aimed to analyze the development of cultural actions in state school libraries located in the municipality of Cacoal - Rondônia, observing their sociocultural dimensions, based on the perceptions of librarians and students at the researched institutions. To support the analytical work, we brought considerations around the understandings of culture and mediation, mediation and cultural action in Information Science and the library as a space for cultural action. As a research methodology, we opted for a qualitative and exploratory approach, using as a methodological procedure: bibliographical survey, preliminary immersion in the field of study - visiting and requesting authorizations from public schools in Cacoalense -, and finally, application of semistructured interviews. We interviewed 5 teachers, who worked as responsible for the libraries and 37 students, from the 7th, 8th and 9th year of Elementary School and 1st, 2nd and 3rd year of High School, from 6 state and urban public schools. The interviews were analyzed using Content Analysis, comparing the results with anthropology and cultural action theorists and recent research related to cultural action and school libraries published in the country, in the context of Information Science. In our results we present: i. Characterization of existing cultural actions in school libraries, focusing on activities and projects carried out and involvement of the school community; ii . Perception of librarians and students about cultural actions existing in school libraries, focusing on the meanings of cultural actions for teachers and students and cultural actions and sociocultural transformations. From this presentation, we highlight that: the school libraries visited and included in the research do not have bachelor's degrees in library science; the activities carried out in the school libraries analyzed are mainly aimed at promoting reading through playful activities, guided by the school's own degree professionals, not necessarily readapted; library infrastructure in general is precarious, with examples of robust and differentiated actions when supported by the community of student parents and companies; the participation of children and young people is indicated as productive and stimulating, even if it does not reach everyone; the meanings of cultural actions turn to the appropriation of reading culture; the teachers believe that cultural actions promoted by libraries are capable of generating educational, personal, social and cultural transformations in the student's life, even more so when they have the support of the school community; students address the transformations felt in their school and personal lives. Finally, we reflect on the results of actions developed in school libraries and indicate that cultural actions should focus on the protagonism and emancipation of students, the plurality and diversity of their experiences and the creation of dialogical, interactive, intercultural and inclusive productions, based on cultural mediation that takes into account the sociocultural context of the subjects inserted in their respective communities.